Epidemiologia wirusowego zapalenia wątroby typy C w Polsce w latach 2010-2014 = Epidemiology of hepatitis C in Poland in 2010-2014 - Kowalska, Marta Estera; Kalinowski, Paweł; Bojakowska, Urszula Jolanta; Zdolska, Wioleta (Journal of Education, Health and Sport, 2017)
Kowalska Marta Estera, Kalinowski Paweł, Bojakowska Urszula, Zdolska Wioleta. Epidemiologia wirusowego zapalenia wątroby typy C w Polsce w latach 2010-2014 = Epidemiology of hepatitis C in Poland in 2010-2014. Journal of Education, Health and Sport. 2016;6(11):35-45. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163469 http://ojs.ukw.edu.pl/index.php/johs/article/view/3956 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 12.10.2016. Accepted: 27.10.2016. Epidemiologia wirusowego zapalenia wątroby typy C w Polsce w latach 2010-2014 Epidemiology of hepatitis C in Poland in 2010-2014 Marta Estera Kowalska1, Paweł Kalinowski1, Urszula Bojakowska1, 2, Wioleta Zdolska3 1 Samodzielna Pracownia Epidemiologii Uniwersytetu Medycznego w Lublinie 2 Studenckie Koło Naukowe przy Samodzielnej Pracowni Epidemiologii Uniwersytetu Medycznego w Lublinie 3 Absolwentka studiów I° na kierunku Zdrowie Publiczne na Uniwersytecie Medycznym w Lublinie Słowa kluczowe: wirusowe zapalenie wątroby typu C, epidemiologia Key words: hepatitis C, epidemiology Streszczenie Wstęp Wirusowe zapalenie wątroby typu C (WZW) jest chorobą wątroby wywoływaną przez wirus zapalenia wątroby typu C. Wirus ten odkryty został w 1989 roku, jako wirus RNA z rodziny Flaviviridae, rodzaju Hepacivirus i może powodować zarówno ostre jak i przewlekłe infekcje wirusowe o różnym nasileniu. Cel pracy Celem pracy była analiza występowania wirusowego zapalenia wątroby typu C w Polsce w latach 2010-2014. Materiał i metody Materiałem analizowanym w pracy były przypadki wirusowego zapalenia wątroby typu C zarejestrowane w Polsce w latach 2010-2014 z uwzględnieniem płci, wieku i miejsca zamieszkania zakażonych publikowane w formie biuletynów rocznych „Choroby zakaźne i zatrucia w Polsce” przez Narodowy Instytut Zdrowia Publicznego - Państwowy Zakład Higieny w Warszawie. Wyniki W badanym okresie zanotowano wzrost liczby przypadków wirusowego zapalenia wątroby typu C w Polsce. Najwięcej przypadków notuje się w grupie wieku powyżej 50 lat. Summary Introduction Hepatitis C (HCV) is a liver disease caused by hepatitis C virus was discovered in 1989 as RNA virus of the family Flaviviridae, genus Hepacivirus and can cause both acute and chronic viral infections of varying severity. Aim The aim of this study was to analysis of incidence of hepatitis C in Poland in 2010-2014. Material and methods The material analyzed in the work were cases of hepatitis C registered in Poland in 2010-2014, taking into account gender, age and place of residence infected published in the form of annual bulletins "Infectious diseases and poisoning in Poland by the National Institutes of Health in Warsaw. Results In the analyzed period saw an increase in the number of cases of hepatitis C in Poland. Most cases are recorded in the age group over 50 years.